Posttraumatic stress disorder after motor vehicle accidents: 3-year follow-up of a prospective longitudinal study. - Mayou, R; Ehlers, A; Bryant, B (2002)
The paper presents a 3-year follow-up of a prospective longitudinal study of posttraumatic stress disorder (PTSD) after motor vehicle accidents (J. Abnormal Psychol., 107 (1998) 508). Participants were 546 patients who had been assessed when attending an emergency clinic shortly after a motor vehicle accident, and at 3 months and 1 year afterwards. The prevalence of posttraumatic stress disorder PTSD at 3 years was 11%. Maintaining psychological factors, i.e. negative interpretation of intrusions, rumination, thought suppression and anger cognitions, were important in predicting the persistence of PTSD at 3 years, as were persistent health and financial problems after the accident. Other predictors were female sex, hospital admission for injuries, perceived threat and dissociation during the accident, and litigation.